Pengaruh Kepemimpinan, Motivasi, dan Lingkungan Kerja terhadap Kinerja Karyawan Java in Coffe & Resto Sumenep - Ilfatul Hasanah; Jamil, S. Hikmah; Zahro, Karimatus (Alkasb: Journal of Islamic Economics, 2022)
Human resources are one of the most important factors in determining the success and sustainability of the company. If the employee's performance is good, the company's goals will be easily achieved. Therefore, the company must need a leader who is able to influence the movement of employees in order to produce a good performance. The purpose of this study was to examine the effect of leadership, motivation, and work environment on employee performance. The type of research used is quantitative research. The population of this research is the employees of Java In Coffee & Resto Sumenep. The sample used was 31 respondents with a saturated sample approach. This study uses multiple linear regression analysis using the SPSS 21.0 program. The results showed that the leadership variable, motivation, had a positive and significant effect on employee performance, while the work environment had a negative and significant effect on employee performance.